The Implementation of Marketing Mix Strategy in Marketing Educational Services at Raudhatul Athfal Al Muttaqin Cirebon - Rahmiati, Ati; Fajriyah, Euis (CV. Strata Persada Academia, 2024)
Implementing the 7P marketing mix strategy in marketing educational services at RA Al Muttaqin aims to determine how the marketing strategy is implemented at the RA Institution. This study uses qualitative research with data collection techniques such as observation, interview, and documentation. Data analysis includes data presentation, data reduction, and conclusion. The results show that RA Al Muttaqin uses the 7P marketing mix strategy in marketing educational services, which includes product, price, place, promotion, people, physical evidence, and process. The product offered is an Islamic school with local wisdom. The price offered is affordable and light enough to meet needs. The place is strategically located near the highway and has a large yard. Promotion uses social media, word of mouth, and flyers as the main promotional media. People include educators and education personnel who are recruited with certain qualifications. The physical evidence provided is complete and according to needs. The learning process is in accordance with the learning plan and is running quite effectively.